Mahmoud Darwish’s Political Views After the Oslo Agreement in the Poetry “Khilaf Ghayru Lughawi, Ma’a Imri al-Qais”: A Semiotics Study - Muhammad Bachrul Ulum (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2021)
This study attempted to analyse Mahmoud Darwish’s political ideas in his book Khilaf Ghairu Lughawi Ma’a Imri’il Qais. He wrote the poem in 1995, two years after the signing of the Oslo Agreement. It was born out of Darwish’s disappointment with the political decision of the Palestine Liberation Organization, which he considered having neglected the priorities of the struggle for independence and territorial claims to the security of Palestinian refugees abroad. This study relied on the qualitative approach to get the intended research results. This study relied on the method of analysis by semiotic analysis of Michael Riffaterre. The results of this study are many uses of Darwish’s metaphorical expressions in his poem, as an irony for policymakers and people were considered deviants from the scale of national priority. His views embodied the disappointment of a political decision of the Palestine Liberation Organization from the hands of Yasser Arafat. He believed Arafat had included Israeli requirements and advantages in that agreement to facilitate the affairs of the Palestinians and the efforts of the victims of past wars.